2014
DOI: 10.1002/jemt.22351
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the eyeball from the humpback whale (Megaptera novaeangliae)

Abstract: Aquatic mammals underwent morphological and physiological adaptations due to the transition from terrestrial to aquatic environment. One of the morphological changes regards their vision since cetaceans' eyes are able to withstand mechanical, chemical, osmotic, and optical water conditions. Due to insufficient information about these animals, especially regarding their sense organs, this study aimed to describe the morphology of the Humpback whale (Megaptera novaeangliae) eyeball. Three newborn females, strand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
(62 reference statements)
1
11
0
Order By: Relevance
“…Our description of the eye in the humpback whale is also in accordance with the results of Rodrigues et al [2014] for the same species. Some of the characteristic features of cetacean eyes, especially those of the larger species, are a flattened, thickened cornea, heavily thickened sclera, spherical or near-spherical lens, highly vascularised fibro-adipose bundle surrounding the optic nerve at the back of the eye, and the reflective choroidal tapetum lucidum Supin, 2007, 2009].…”
Section: Eye Morphology and Tapetumsupporting
confidence: 78%
See 2 more Smart Citations
“…Our description of the eye in the humpback whale is also in accordance with the results of Rodrigues et al [2014] for the same species. Some of the characteristic features of cetacean eyes, especially those of the larger species, are a flattened, thickened cornea, heavily thickened sclera, spherical or near-spherical lens, highly vascularised fibro-adipose bundle surrounding the optic nerve at the back of the eye, and the reflective choroidal tapetum lucidum Supin, 2007, 2009].…”
Section: Eye Morphology and Tapetumsupporting
confidence: 78%
“…In this study, we found the Bryde's whale and the humpback whale lenses to be non-spherical, with the axial diameter of the lens being approximately 30% shorter than the naso-temporal and dorso-ventral diameters. Similarly, Rodrigues et al [2014] also found that the axial diameter of the lens in the humpback whale was closer to 40% shorter than the naso-temporal and dorso-ventral diameters. Moreover, Zhu et al [2001] and Buono et al [2012] found that the lens axial diameter was substantially shorter than the naso-temporal and dorsoventral diameters in two other mysticete species, the bowhead whale and the southern right whale, respectively.…”
Section: Eye Morphology and Tapetummentioning
confidence: 82%
See 1 more Smart Citation
“…For example, the eyeballs of the gray whale are situated lateral and external to the bony orbit, which has been observed in another mysticete ( Eubalaena glacialis (Buono et al, ). However, in a humpback ( Megaptera novaeangliae ) the eyeball is reportedly located within the orbit (Rodrigues et al, ). Compared to a similar sized right whale calf, the gray whale eyeball is nearly twice as long (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to studies of the eye morphology of the southern right whale (Buono et al, ). The bowhead (Zhu et al, ) and the humpback (Rodrigues et al, ) and irrespective of ontogenetic age, the gray whale eyeball is shorter mediolaterally (width) than in either dorsoventral (height) or rostro‐caudal (length) directions (Table ). Unfortunately, anatomy of internal ocular structures and histological samples of the retina were unavailable for comparative purposes and determination of visual acuity of Eschrichtius .…”
Section: Discussionmentioning
confidence: 99%